DESIGN OF A 4 BAND COLOR CODE RESISTOR CALCULATOR APPLICATION BASED ON THE JAVA PROGRAMMING LANGUAGE - Siregar, Rahmat Fauzi; Al-Khowarizmi, AK; R, Rohana; A, Affandi; Nasution, Arya Rudi (RELE (Rekayasa Elektrikal dan Energi) : Jurnal Teknik Elektro, 2024)
This research aims to design and develop a 4 band resistor color code calculator application based on the Java programming language. This calculator is designed to help electronics technicians identify resistor values based on the color code found on 4 band resistors. This application provides an intuitive and user-friendly interface that allows users to enter the color of each band on a resistor and quickly displays the corresponding resistance value. Apart from that, this application can also provide the tolerance of a given resistor. The development method used in this research includes needs analysis, user interface design, implementation of resistance value calculation algorithms, and application testing. This application is implemented using the Java programming language and supported by the JavaFX graphic library to create an attractive interface. Test results show that this application can calculate resistance values accurately and is responsive to user input. With this application, it is hoped that users can easily and quickly identify the resistance value of 4 band resistors, increase efficiency in their work, and reduce the possibility of errors in deciphering resistor color codes.